Meningkatkan Ketahanan Ruang Udara Indonesia melalui Analisis Intelijen - Hadisiswanto Putro, Laksono; Tjandra, Celine; Nursirwan, Nursirwan (Jurnal Kajian Stratejik Ketahanan Nasional, 2024)
Airspace defense is part of the country's sovereignty and its existence has been recognized. However, Indonesia does not yet have a law governing its airspace. This lack of regulation has occurred since the country's independence in 1945. This study aims to determine the benefits and urgency of improving airspace resilience in Indonesia by using an intelligence analysis approach. The research method is qualitative and descriptive analytical. Intelligence analysis is a powerful tool to anticipate and mitigate threats. By conducting intelligence analysis, it means being able to predict upcoming threats. The results of this study show that intelligence analysis is very useful for airspace defense with the addition of twelve air radars, which will help narrow the space for cyber threats. In addition, intelligence activities related to data collection, aerial observation, aerial reconnaissance, and prevention of attacks on the country's territory have also been introduced.